The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1007/s00170-021-06602-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel double-side welding approach for friction stir welding of polypropylene plate

Abstract: In almost every industry, polymer materials are in high demand in recent years due to their lightweight and easy formability. However, eco-friendly, cost-efficient and defect-free joining of polymers is a major concern. In this article, a novel approach is taken for friction stir welding of polypropylene by implementing a double-side welding technique. The effect of tool rotational speed on construction and properties of the welded joints are studied. The torque and forces exerted on the tool during double-sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…On the other hand, the double-sided pass technique in FSW has been proven to improve joint quality and mechanical performance. It leads to smaller defect-free joints and higher tensile strength, as per previous research (Arici & Sinmaz, 2005;Nath et al, 2021). This technique improves material consolidation and homogenization across the joint interface, forming a defect-free weld zone with enhanced metallurgical bonding and structural integrity.…”
Section: Hdpe Plate Fsw-ed Jointmentioning
confidence: 56%
See 2 more Smart Citations
“…On the other hand, the double-sided pass technique in FSW has been proven to improve joint quality and mechanical performance. It leads to smaller defect-free joints and higher tensile strength, as per previous research (Arici & Sinmaz, 2005;Nath et al, 2021). This technique improves material consolidation and homogenization across the joint interface, forming a defect-free weld zone with enhanced metallurgical bonding and structural integrity.…”
Section: Hdpe Plate Fsw-ed Jointmentioning
confidence: 56%
“…Figure 7. bottom, reveals that double-side pass welding successfully eliminates root defects (Nath et al, 2021) and increases joint efficiency but leaves a poor surface finish on the bottom surface. Root defects were observed in every single side weld produced in this study (Figure 7.…”
Section: Hdpe Plate Fsw-ed Jointmentioning
confidence: 99%
See 1 more Smart Citation
“…The spot weld pattern was varied with 4-3, 4-5, and 7-6 welds in the first and second pass respectively. In double pass FSSW the overlapping region gets heated and stirred twice resulting in least microhardness as shown in [29], however performing a second pass was necessary to increase overall strength of the joint. In the second group spindle speed (2000 rpm), plunge depth (1 mm), and weld pattern (4-5) were constant and dwell time varied from 40 s to 60 s. It was observed that as the number of spot welds increases, the thermally affected regions start to overlap and result in material sticking to the tool pin.…”
Section: Resultsmentioning
confidence: 99%
“…The feasibility of welding poly(methyl methacrylate) (PMMA) sheets via the FSW process has also been investigated experimentally and theoretically, employing simulation tools [20]. Polypropylene (PP) has also been investigated for FSW [21,22]. The feasibility and the mechanical performance of dissimilar joints of plastics and composites have also been investigated and reported [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%